THE URGENCY OF MAGNETIC DECLINATION IN QIBLA DIRECTION MEASUREMENT USING A COMPASS IN THE IBU KOTA NUSANTARA (IKN) AREA - Alawiya, Balkis Sifara; Fadhel, Muhammad Said (UIN Mahmud Yunus Batusangkar, 2024)
This study analyzes the urgency of correcting magnetic declination in determining the accurate direction of the Qibla, particularly for mosque construction in the area of Ibu Kota Nusantara (IKN), Indonesia. Using a literature review and quantitative approach, magnetic declination data from 1590 to 2024 was collected using the NOAA magnetic declination calculator with the IGRF-13 model at the IKN coordinates. The data was analyzed to identify temporal and spatial variations and then visualized using LabPlot software. The results show significant changes in magnetic declination that affect the accuracy of the Qibla direction if not corrected. The total percentage of magnetic declination values beyond the tolerance limit or iḥtiyāṭ al-qiblah (0.4º) is 77.18%. This study emphasizes the importance of using reliable declination calculators from credible institutions such as NOAA and visualization tools to ensure that the Qibla direction aligns with technical and Sharia standards, making it a guide for urban planning in IKN, especially in determining the direction of public buildings such as mosques, schools, and government offices.